Rwanda : Enhanced Initiative for Heavily Indebted Poor Countries-Completion Point Document. (IMF Staff Country Reports; Country Report ;, 2005)
This paper presents the Completion Point Document for consideration of Rwanda's Enhanced Initiative for Heavily Indebted Poor Countries. The government has maintained the policy of protecting social sector budget allocations from cuts during the course of the fiscal year, and military spending has progressively been reduced, which has also enabled a reallocation of resources to priority areas. Moreover, since the 2002 budget cycle, expenditures have been classified in all ministries according to programs and sub-programs, expected outputs, activities, and inputs.